The mosquitoes of Quintana Roo state, Mexico (diptera: culicidae) - Ortega Morales, Aldo I.; Mis Avila, Pedro; Elizondo-Quiroga, Armando; Harbach, Ralph E.; Siller-Rodríguez, Quetzaly K.; Fernández-Salas, Ildefonso (Instituto de Ecología, A.C., 2010)
A study on the distribution of the mosquitoes of Quintana Roo State of México was carried out by collecting immature and adult stages during September and October 2006. The collections were made from different locations in the three physiogeographical provinces of the state: Carso Yucateco, Carso, Lomeríos de Campeche, and Costa Baja de Quintana Roo. A total of 420 larvae, 294 pupae, and 726 adults representing 13 genera and 41 species were collected. Two genera, three subgenera, and 11 species are new to the mosquito fauna of Quintana Roo State. Collection and bionomical data are included for species collected during the study, and a checklist of species newly and previously recorded from the state is provided.